1998
DOI: 10.1038/sj.onc.1201946
|View full text |Cite
|
Sign up to set email alerts
|

Excision of mismatched nucleotides from DNA: a potential mechanism for enhancing DNA replication fidelity by the wild-type p53 protein

Abstract: The tumor suppressor p53 plays a critical role in the regulation of the cell cycle and the maintenance of genetic stability. The 3'?5' exonuclease activity of p53 has recently been recognized as a novel biochemical function of this molecule, but the biological signi®cance of this activity remains elusive. Using an in vitro DNA replication assay with puri®ed human DNA polymerases, p53 protein, and de®ned DNA primer/templates, we demonstrated that the wild-type (wt) p53 protein, but not the mutant p53 protein, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 42 publications
2
93
0
Order By: Relevance
“…Moreover, pol a can be a nity-puri®ed together with p53 from monoclonal antibody columns directed against pol a (F Grosse, unpublished observations). Furthermore, Huang (1998) recently showed that wt p53, but not mutant p53, speci®cally enhanced the replication ®delity of polymerase a in an in vitro replication assay, strongly supporting the idea that p53 can act as an exogenous proofreader for this replicase. However, further experimentation is necessary to con®rm and extend these initial ®ndings.…”
Section: Possible Functions Of the P53 Exonuclease Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, pol a can be a nity-puri®ed together with p53 from monoclonal antibody columns directed against pol a (F Grosse, unpublished observations). Furthermore, Huang (1998) recently showed that wt p53, but not mutant p53, speci®cally enhanced the replication ®delity of polymerase a in an in vitro replication assay, strongly supporting the idea that p53 can act as an exogenous proofreader for this replicase. However, further experimentation is necessary to con®rm and extend these initial ®ndings.…”
Section: Possible Functions Of the P53 Exonuclease Activitymentioning
confidence: 82%
“…Therefore, DNA polymerases a and b are particularly error prone and until now it is not known, how mismatched nucleotides incorporated by these two polymerases are removed (Kunkel, 1992). Moreover, both polymerases have a strong tendency to introduce frame-shift mutations by misinsertion or deletion of nucleotides (Huang, 1998). Since p53 recognizes DNA bulges caused by insertion/ deletion mismatches (Lee et al, 1995), it might be particularly suited to excise them via its 3'-45' exonuclease.…”
Section: Possible Functions Of the P53 Exonuclease Activitymentioning
confidence: 99%
“…®vefold better than ssDNA. p53 has been described to exonucleolytically degrade ssDNA in a 3' ± 45' orientation up to 3-mer end products (Mummenbrauer et al, 1996;Jean et al, 1997;Huang 1998). To unequivocally demonstrate exonuclease activity directed towards 3-stranded junction DNAs and to determine the directionality, we prepared substrate DNAs, which were either 32 Plabeled at the 5'-end (Figure 2b) or at the 3'-end of the`top'-oligonucleotide (Figure 2c), and analysed the p53-dependent degradation pattern by denaturing polyacrylamide gel electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical studies (Mummenbrauer et al, 1996;Jean et al, 1997;Huang, 1998;Janus et al, 1999b) provided evidence for a 3' ± 45' exonuclease activity intrinsic to p53, which might have functions in ®delity control of DNA replication or in DNA repair. In the analysis presented here, we carried out hRad51-dependent strand exchange reactions, to analyse functional interactions with p53.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here imply that p53 can maintain genome integrity by suppression of spontaneous HR independently of the G1/S checkpoint and probably also in the absence of transcriptional activation. Furthermore, p53 has been suggested to act in a post-replicative mismatch repair pathway (Mummenbrauer et al, 1996;Huang, 1998), it co-localizes with DNA synthesis and the DNA replication apparatus (Huang, 1998), interacts with viral replication (Deppert, 1994), migrates into the nucleus with S phase (Shaulsky et al, 1990;Martinez et al, 1991), and interacts with a variety of proteins involved in DNA repair (for further review, see Janus et al, 1999a). Deppert and colleagues (Janus et al, 1999b) recently made the intriguing observation that p53's exonuclease and sequencespeci®c DNA binding activities appeared to be mutually exclusive functions.…”
Section: How Does P53 Regulate Homologous Recombination?mentioning
confidence: 99%